IMPLEMENTATION OF COMPENSATION FOR LOSS OF OFFICIAL VEHICLES IN ROKAN HILIR DISTRICT - syahri, alfi; ardiansah, ardiansah; Kadaryanto, Bagio (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Article 7 of Government Regulation Number 38 of 2016 concerning Procedures for Compensation Claims for State/Regional Losses Against Non-Treasurer Civil Servants or Other Officials, states that: